Impact of the Russia-Ukraine war on the energy sector in southeast asia - Ilman, Nauvan Zam; Anam, Muhammad Zahrul (Universitas Islam Malang, 2023)
The conflict between Russia and Ukraine has spread, having a variety of implications on the global community. Where the world's two biggest energy producers are at conflict with one another. In this research, topics like